2016
DOI: 10.1016/j.jtcvs.2016.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and ventilatory responses during exercise in chronic thromboembolic disease

Abstract: Patients with CTED showed an abnormal pulmonary vascular response to exercise and a decreased ventilatory efficiency. Responses after PEA point to restoration of right ventricle stroke volume response and ventilatory efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 34 publications
1
59
0
1
Order By: Relevance
“…Thus, while it is known that patients who develop chronic pulmonary vascular obstruction have significant symptoms,22 our study highlights that exercise limitation may exist even in the absence of chronic imaging abnormalities indicative of vascular compromise. Why baseline imaging parameters, such as abnormal pulmonary artery diameter, appeared to be more prognostic than follow‐up imaging parameters is uncertain, although our study patients had normalization of most imaging parameters by 12 months.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, while it is known that patients who develop chronic pulmonary vascular obstruction have significant symptoms,22 our study highlights that exercise limitation may exist even in the absence of chronic imaging abnormalities indicative of vascular compromise. Why baseline imaging parameters, such as abnormal pulmonary artery diameter, appeared to be more prognostic than follow‐up imaging parameters is uncertain, although our study patients had normalization of most imaging parameters by 12 months.…”
Section: Discussionmentioning
confidence: 68%
“…Patients with chronic thromboembolic disease with and without pulmonary hypertension show an abnormal pulmonary vascular response to exercise and decreased ventilatory efficiency. PEA is a treatment of choice in surgically accessible CTEPH: responses after PEA point to a restoration of right ventricle stroke volume, ventilatory efficiency and exercise capacity [2,32,33]. Patients with more severely depressed exercise capacity at baseline display a relatively greater degree of functional recovery after PEA.…”
Section: Discussionmentioning
confidence: 99%
“…They experienced improved symptoms as well as improved functional class and quality of life postoperatively without in-hospital mortality, although at a cost of major complications such as reintervention, pneumothorax requiring chest drain insertion, small subdural hematomas, re-intubation and tracheostomy in 40% of patients. Another study confirmed that PEA can reduce exertional dyspnea and improve exercise tolerance in patients with CTED [94]. Although early surgical pulmonary endarterectomy can also be performed to prevent the development of secondary microvasculopathy and progression to CTEPH, the natural history of the disease is unknown and there is no evidence that CTED evolves into CTEPH.…”
Section: Ctedmentioning
confidence: 96%
“…The exercise limitation has been attributed either to exercise-induced pulmonary hypertension or to deadspace ventilation. An abnormal pulmonary vascular reserve, illustrated by an increased slope of the pressureflow relationship [94] and decreased ventilatory efficiency, with increased ventilatory equivalents for carbon dioxide (VE/VCO2), has been reported in CTED patients [19,94]. A reduced RV contractile reserve is associated with the abnormal pulmonary vascular reserve [95].…”
Section: Ctedmentioning
confidence: 99%
See 1 more Smart Citation